EXPERIENCE IN ORGANIZING PATRIOTIC EDUCATION AT CLASSICAL UNIVERSITY - Oleg N. Shirokov; Tatyana N. Ivanova; Rustem A. Idrisov; Dmitriy A. Yaltaev; Sergey N. Kodybaykin (Moscow Polytechnic University, 2016)
The article describes the experience of the educational work of the lecturers of historical-geographical faculty of the CSU of I.N. Ulyanov. A combination of manifold forms and methods in this area of educational activity ensures its efficiency. CSU of I.N. Ulyanov was the first university to introduce for all first-course students the discipline "Civic studies and patriotic education" aimed at formation of socially active persons ready for performance of civic duties.